Lock Gates and Other Closures in Hydraulic Projects - Daniel, Ryszard, author 649531; Paulus, Tim, author 649532; ScienceDirect (Online service) 7722 (Amsterdam : Butterworth-Heinemann, 2019)
Lock Gates and Other Closures in Hydraulic Projects shares the authors practical experience in design, engineering, management and other relevant aspects with regard to hydraulic gate projects. This valuable reference on the design, construction, operation and maintenance of navigation lock gates, movable closures of weirs, flood barriers, and gates for harbor and shipyard docks provides systematic coverage on all structural types of hydraulic gates, the selection of gate types, and their advantages and disadvantages. The discussion includes the latest views in new domains, such as environmental impact of hydraulic gate projects, sustainability assessments, relation with the issues of global climate change, handling accidents and calamities, and the bases of asset management. Heavily illustrated, this reference provides a generous amount of case studies based on the author’s own and their colleagues’ experiences from recent projects in Europe, America and other continents.